2012
DOI: 10.15174/au.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Petrografía y distribución de óxidos de Fe, Al y Si en fragipanes blancos de origen volcánico

Abstract: El objetivo fue determinar la petrología y distribución de óxidos de Fe, Al y Si en tres perfiles de suelos de origen volcánico con horizontes endurecidos (fragipán), en la región noroeste del Estado de México. Se utilizaron técnicas químicas selectivas para extraer Fe, Al y Si. El fragipán blanco clasifica petrográficamente como toba dacítica poco soldada y alterada. Los perfiles muestran incipiente a moderado grado de alteración de minerales primarios que contienen Fe y Al dadas las condiciones climáticas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…Acevedo et al (2014) indicated that Feox is usually present in soils with pH-dependent charges and a high P fixation capacity; this coincides with the characteristics of the parental material of the soil in the present study. Acevedo-Sandoval et al (2002) reported that Feox predominates in the upper horizons of Inceptisols and Alfisols. In our study, this parameter showed a higher coefficient of variation compared with Fed and Fet in both horizons.…”
Section: Selective Extractions Of Available Amorphous and Total Fementioning
confidence: 99%
See 1 more Smart Citation
“…Acevedo et al (2014) indicated that Feox is usually present in soils with pH-dependent charges and a high P fixation capacity; this coincides with the characteristics of the parental material of the soil in the present study. Acevedo-Sandoval et al (2002) reported that Feox predominates in the upper horizons of Inceptisols and Alfisols. In our study, this parameter showed a higher coefficient of variation compared with Fed and Fet in both horizons.…”
Section: Selective Extractions Of Available Amorphous and Total Fementioning
confidence: 99%
“…Some Fe ratios are used to determine the presence of these minerals in the soil. For example, Feox:d is a measurement of the amount of total pedogenic Fe, while the difference, Fed-ox, is used to estimate crystallized Fe (goethite and hematite) (Acevedo-Sandoval et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The studied soils and hardened horizons are located at the Tarango Formation, which is constituted by volcanic ash, pumice, lava, and dacitic tuff deposits (Pliocene-Pleistocene). The most important minerals present in the soils are quartz, feldspar, chlorite, calcite, volcanic glass, and lithic fragments in the clay fraction (Acevedo-Sandoval et al, 2002. The morphological description of the seven profiles is presented in Table 1.…”
Section: Study Areamentioning
confidence: 99%
“…All these features represent a limiting factor in regard to plant development, restricting root penetration, which devaluates or impedes its agricultural use. Pyrogenic materials mainly form hardened horizons: volcanic glass, quartz, pyroxene, mica, plagioclase, alkali feldspar and iron oxide, as well as authigenic minerals: halloysite, kaolinite, montmorillonite, allophane, hydrated iron oxides and aluminum and silicon sesquioxide, among others (Acevedo-Sandoval et al, 2003Gama-Castro et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Toda una batería de métodos, cuyo objetivo común es la compleja identificación de los distintos óxidos y oxihidróxidos de hierro presentes en los suelos; algunos de los cuales son metaestables como akaganetita y ferrihidrita. Acevedo-Sandoval et al (2002), mediante el uso de las técnicas de extracción de Fe indican que los óxidos de Fe cristalino se incrementan en relación con la profundidad, mientras que los amorfos predominan en los horizontes superiores. El uso de espectroscopía Mössbauer aplicada al estudio de la mineralogía magnética en secuencias de loess/paleosuleos de la región pampeana, permitió constatar cierto incremento de hematita en los niveles más pedogenizados (Terminiello et al, 2001;.…”
Section: Paleosuelosunclassified